Sweet potato processing technology - Mu, Taihua; Sun, Hongnan; Zhang, Miao; Wang, Cheng (Academic Press, 2017)
Sweet Potato Processing Technology systematically introduces processing technologies of sweet potato starch and its series products including sweet potato protein, dietary fibers, pectin, granules, anthocyanins and chlorogenic acids. The book provides a detailed and comprehensive account of physicochemical and functional properties of sweet potato products, the nutritional components extracted from sweet potato, as well as their utilization in food, medicine and cosmetic fields. This book can provide the scientific basis and technical support for virtuous circle promotion and structure upgrade of sweet potato processing industry. This book will be a valuable reference for undergraduate and graduate students, as well as specialists and enterprise research staff in the field of food technology.